Produksi Rumput Gajah (Pennisetum purpureum) yang Diberi Pupuk N, P dan K dengan Dosis 0, 50 dan 100% pada Devoliasi Hari ke-45 - Seseray, Daniel Yohanis; Santoso, Budi; lekitoo, Marlyn Nelce (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2013)
Production of elephant grass (Pennisetum purpureum) would be better if fertilized with the proper doses and appropriate. This study aimed to determine the production of fresh matter, dry matter, ratio of grass stems and leaves, dry matter and organic matter of elephant grass given fertilizer N, P and K with the doses of 0%, 50% and 100% at defoliation at 45th day. This study used an experimental method of randomized block design experiment consisted of 5 and 3 treatmentsgroups, so there were 15 experimental units. The treatments used were: Treatment 1 (control/not fertilizer), Treatment 2 (100 kg Urea/ha; 50 kg TSP/ha; 50 kg KCl/ha) and Treatment 3 (200 kg Urea/ha, 100 kg TSP/ha: 100 kg KCl/ha). The results showed that the doses of fertilization treatments did not significantly (P≥ 0,05) affect the fresh matter, dry matter, ratio of grass stems:leaves, dry matter and organic matter value of elephant grass at the first harvest aged 45th day. Treatment 2 and 3 increased forage the fresh matter production by 29.86% and 28.51%, respectively, while production of dry matter by 28.85% and 30.77% compared to treatment 1 (control). The ratio of grass stems and leaves varied between 59.1 - 61.26%:38,7 - 40, 9%. Organic matter content tended to increase with increasing doses of N, P and K fertilizer.Key words : elephant grass production, N, P, and K fertilizer, fertilizer doses